Effects of feeding low-protein diets fortified with amino acids on broiler chickens under high environmental temperatures - Mohamed, Elmutaz Atta Awad (2016)
Feeding amino acids (AA) fortified low-protein diets is of interest to poultry nutritionists because of the ability to reduce feed cost, environmental pollution, and effect of heat stress on birds. However, it is still unclear to what extent the AA fortification can replace the crude protein (CP) without affecting the broiler performance, especially under high environmental temperatures. Hence, this study aimed at determining the effect of using crystalline AA to lower CP in broilers diets on growth performance, carcass characteristics, internal organs weights, blood metabolites, and physiological responses of broilers under high environmental temperatures. Five experiments were conducted; Experiments 1 through 3 were conducted with day-old male broilers under the tropical climate (22-33°C and 70-90% relative humidity) from 1-21 days (starter period). In Experiment 1, five isocaloric diets were formulated in a gradual CP decline from 22.2% to 16.2% at 1.5% intervals. Weight gains (WG) were suppressed by feeding 16.2 and 17.7% CP. Feeding 16.2% CP reduced serum total protein (TP), uric acid (UA), and increased triglyceride (TG). Heart weights increased but no changes in liver and abdominal fat weights. Experiment 2, the ability of non-essential amino acids (NEAA) or further essential amino acids (EAA) fortification to overcome the poorer performance in birds fed 16.2% CP was evaluated. Five diets were formulated: (i) 22.2% CP (positive control; PC) (ii) 16.2% CP + all EAA to meet the requirements, negative control (NC) (iii) through (v) were obtained by supplementing NC diet with EAA, NEAA, or EAA+NEAA to equal the AA levels in the PC, respectively. Fortification with EAA alone, only improved FI, whereas, NEAA or EAA + NEAA enhanced the WG and FI. Experiment 3 was conducted to find out whether all NEAA or a single NEAA was behind the restored performance in experiment 2. Eight diets were formulated: (i) PC; (ii) NC; (iii) NC + glycine (Gly); diets (iv) through (vii) were obtained by supplementing NC diet with individual glutamic acid, proline, alanine, or aspartic acid, respectively; (viii) NC + all NEAA. Among individual NEAA, only Gly had the potential to improve the growth performance of birds. In Experiment 4, an equal number of male and female broilers were assigned to five diets (PC, NC, and more three diets obtained by supplementing the NC diet with higher Gly concentrations) for a starter and grower (22- 42 days) feeding periods under tropical climate. No significant diet × gender interaction was observed for all the parameters measured. Results for WG and FI showed that birds were more responsive to additional Gly fortification during grower period, where a significant linear response to improving WG and FI was observed with increasing Gly levels. Diet effect was significant for performance parameters, proportional liver and abdominal fat weights, TG and UA, and litter moisture and nitrogen contents. The gender effect was significant for performance parameters, abdominal fat, and litter’s moisture and nitrogen. In Experiment 5, from 1 – 21 days, an equal number of birds were fed either (i) a normal-protein diet or (ii) Gly fortified low-CP diet, under optimum temperatures. On day 22, the total birds from the starter period were redistributed into 12 treatments in a 4 × 3 factorial arrangement {(4 diets: (i) normal-protein during the starter and grower periods, NPNP; (ii) normal-protein during the starter and low-CP diet during the grower period, NPLP; (iii) low protein-CP diet during the starter and normal-protein during the grower, LPNP; (iv) low-CP diets during both periods, LPLP)} × {(3 thermal treatments (i) unheated, constant 23±1°C; (ii) cyclic heated, cyclic 34±1°C for 7 hours; and (iii) constant heated, constant 34±1°C)}. During the starter period, feeding low-CP diet resulted in growth performance equal to those birds fed normal-protein diet. During the grower period, there were significant diet × temperature interactions for growth performance, intestinal morphology and microbial, and triiodothyronine (T3) parameters. Feeding low-CP diet under constant heat stress resulted in poorer growth performance; lower intestinal Lactobacillus and higher Clostridium; as well as lower T3. On contrast, feeding low-CP diet under unheated, and cyclic heat stress resulted in growth performance; intestinal microbial populations and morphology parameters equally well to those fed normal-protein diet as well as higher T3. Together, it can be concluded that by using EAA, protein in broilers starter diet can be reduced to 19.2% under tropical climate. The addition of extra EAA may not improve the suppression in performance. However, fortification with Gly may improve but not support overall standard growth performance under tropical climate. The Gly fortified low-CP diets can be fed to broilers under acute heat stress without any adverse effects.